The Fourth Lifeway: Recognizing the Legacy of Bodily Difference and Disability within the Inka Empire - Ryan Scott Hechler (Disability Studies Quarterly, 2022)
No abstract available.
Keywords: Inkas; Tawantinsuyu; Quechua; Andes; Spanish Colonialism; Peru; Bolivia; South America; Latin America; Ethnohistory; Indigenous Studies